Light Scattering By Optically-Trapped Vesicles Affords Unprecedented Temporal Resolution Of Lipid-Raft Dynamics - Liam Collard (Nature Portfolio, 2017)
Abstract A spectroscopic technique is presented that is able to identify rapid changes in the bending modulus and fluidity of vesicle lipid bilayers on the micrometer scale, and distinguish between the presence and absence of heterogeneities in lipid-packing order. Individual unilamellar vesicles have been isolated using laser tweezers and, by measuring the intensity modulation of elastic back-scattered light, changes in the biophysical properties of lipid bilayers were revealed. Our approach offers unprecedented temporal resolution and, uniquely, physical transformations of lipid bilayers can be monitored on a length scale of micrometers. As an example, the deformation of a membrane bilayer following the gel-to-fluid phase transition in a pure phospholipid vesicle was observed to take place across an interval of 54 ± 5 ms corresponding to an estimated full-width of only ~1 m°C. Dynamic heterogeneities in packing order were detected in mixed-lipid bilayers. Using a ternary mixture of lipids, the modulated-intensity profile of elastic back-scattered light from an optically-trapped vesicle revealed an abrupt change in the bending modulus of the bilayer which could be associated with the dissolution of ordered microdomains (i.e., lipid rafts). This occurred across an interval of 30 ± 5 ms (equivalent to ~1 m°C).